EFEKTIFITAS PEMBERIAN JUS TOMAT TERHADAP LINGKAR PERUT DAN LEMAK TUBUH PADA TENAGA KESEHATAN DENGAN OBESITAS - Florentinus Nurtitus; Agung Susanto; Tonang Ardyanto (PERSATUAN AHLI GIZI INDONESIA, 2022)
Obesity is an excess weight that is characterized by the Body Mass Index (BMI) 27kg/m2. Obesity in health professionals can potentially endanger health professionals. Tomatoes are a source of lycopene which has a protective effect against obesity. This study aims to analyze the effect of giving tomato juice on the waist circumference and body fat of health officers with obesity. This experimental study employed the pre-test and post-test control group design. The research sample comprised 66 individuals, divided into 2 groups. The Control group was given education on a low-calorie diet while the treatment group was given education on a low-calorie diet and 500 ml of tomato juice. The data analysis was conducted using paired–t-tests. After 30 days of treatment, there was a decrease in body fat levels in the treatment group by 1.32+1.4 (p=0.000). Meanwhile, in the control group, there was no significant difference (p=0.543). The treatment group experienced a decrease in waist circumference by 5+0.44 (p=0.000) and the control group had a difference of 3.12+2.61 (p=0.000). Tomato juice is effective in reducing waist circumference and body fat in obesity. It is necessary to consider the use of tomato juice in programs aimed at reducing waist circumference and body fat.